Pengaruh Pengaruh Model Contextual Teaching Learning (CTL) dengan Media Video YouTube Terhadap Kemampuan Berpikir Kreatif Siswa pada Pembelajaran IPA Kelas V SD - Hermi Susanti; Irwan Koto (Universitas Bengkulu, 2023)
This This study aims to determine the effect of the Contextual Teaching Learning (CTL) learning model with YouTube video media on the creative thinking abilities of students in science learning in fifth grade elementary school. This research is a quantitative research. The method used is quasy experiment. The design in this study is One Group Pretest and Posttest Design. The population in this study were fifth grade students at SD Negeri 22 South Bengkulu. The sample in this research is 21 VA students. The instrument used in the form of written tests consisted of dimensions of fluent thinking ability, flexible thinking ability, original thinking ability, detailed thinking ability, and thinking ability to judge. Research data using inferential analysis paired Samples T-Test with the help of SPSS 16.0. The results showed that there was an influence of the Contextual Teaching Learning (CTL) learning model with YouTube video media on the creative thinking ability of students in science learning in grade V elementary school.